Sports Industry During The Covid-19 Pandemic Period (A Case Study Of The Collaboration Between PSSI And Stakeholders) - Uden Kusuma Wijaya (Jurnal Syntax Transformation, 2020)
Football in Indonesia is under the auspices of PSSI (Football Association of Indonesia). During the Covid-19 pandemic, the challenges were thoughtful, including the temporary suspension of the Indonesian League. This situation raised the pros and cons because clubs have to pay and also manage football management during a pandemic. The theory used in this study is organizational innovation theory, and the second is management theory during the Covid-19 pandemic. This qualitative study gained the data collection from secondary sources and also previous research information. This research used the comparative study to analyze the data. By the end of this research, it answered how the PSSI response and what steps were taken by the government, especially the ministries, football clubs and the managements to organize the club and carry out the league again during the Covid-19 pandemic.